Bioactive Properties of Microencapsulated Anthocyanins from Vaccinium floribundum and Rubus glaucus - Carlos Barba-Ostria; Rebeca Gonzalez-Pastor; Fabián Castillo-Solís; Saskya E. Carrera-Pacheco; Orestes Lopez; Johana Zúñiga-Miranda; Alexis Debut; Linda P. Guamán (Molecules)
Anthocyanins, widely recognized for their antioxidant properties and potential health benefits, are highly susceptible to degradation due to environmental factors such as light, temperature, and pH leading to reduced bioavailability and efficacy. Microencapsulation, which involves entrapment in a matrix to enhance stability and bioavailability. This study aims to investigate the bioactive properties of microencapsulated anthocyanins derived from Vaccinium floribundum (Andean blueberry) and Rubus glaucus (Andean blackberry). The extracts from V. floribundum and R. glaucus were microencapsulated using maltodextrin as the carrier agent due to its film-forming properties and effectiveness in stabilizing sensitive compounds through a spray-drying process. The microcapsules were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) to assess their chemical and morphological properties. The biological activities of these microencapsulated anthocyanins were evaluated using in vitro assays for their antibacterial, antioxidant, and anti-inflammatory effects. The results indicated enhanced bioactivity of the microencapsulated anthocyanins, suggesting their potential use in developing functional foods and pharmaceuticals. This study provides valuable insights into the effectiveness of microencapsulation in preserving anthocyanins’ functional properties and enhancing their health-promoting effects, highlighting the potential for application in the food and pharmaceutical industries.